LITERATURE REVIEW ON INTERNATIONAL TRADE NETWORK - Hou Xiaoli; Rini Suryati Sulong (International Journal of Accounting, Finance and Business, 2023)
Using social network analysis method to study international trade can explain the complex network of international trade patterns, reveal its formation mechanism and evolution law, and the status of a country or region in it. This paper reviews the related research on international trade networks. Firstly, seven international trade network construction methods are introduced, including the classical network model, fitness model, hyperbolic model, trade flow network model, multi-layer trade coupling network model, international trade dichotomy network model, and international trade skeleton network model; Then the research objects of the international trade network are classified according to the goods and services of BEC; Finally, the main research contents of international trade network are sorted out from the importance of nodes, the characteristics and evolution of network structure and influencing factors. The main conclusions are as follows: 1) in addition to the classical network model, different network models are derived, which provide research paradigms for trade networks with different perspectives and characteristics; 2) The research object involves all walks of life. In the future, the heterogeneity of the same industry can be investigated and the research of trade network refined; 3) The current trade network mainly presents the characteristics of small world, “core-periphery” and community structure, but the research on the evolution law is not systematic; 4) Based on the CAGE framework, this paper sorts out the impact of cultural, administrative, geographic and economic factors on the international trade network. With the deepening of international bilateral and multilateral cooperation, the development of international trade networks will become more complex. A more systematic and scientific framework should be established for the study of influencing factors.